Avaliação da produção simultânea de xilitol e etanol a partir do bagaço de sisal - Bezerra, Gustavo Santos (2016)
The scientific community has been concerned with environmental issues and the allocation of agro-industrial waste, seeking to perform treatments for waste or recycling to add value. Sisal bagasse is a residue of the sisal, which is discarded into the environment without control. The aim of this study was to evaluate the simultaneous production of xylitol and ethanol from hemicellulose liquor sisal bagasse. The characterization of lignocellulosic biomass was carried out by checking the cellulose, hemicellulose and lignin. The pretreatment was carried out in stainless steel reactor in the ratio 1/10 (bagasse / acid) for 1 hour. To check the influence of temperature variables and concentration of sulfuric acid 22 experimental design with 3 central points was carried out. The liquor hemicellulose hydrolyzate was analyzed by High Performance Liquid Chromatography (HPLC) methods as the levels of sugars and inhibitors and the changes in the treated bagasse were analyzed-Ray Diffraction (XRD), scanning electron microscopy (SEM), thermogravimetry (TG) and Infrared (IR). In the acid treatment model was statistically significant at the 95% confidence level, confirmed by the F test, the response surface indicated that the higher xylose content and glucose were obtained at the maximum level, corresponding to a temperature of 120 °C and 2 5% sulfuric acid. The characterization techniques reaffirmed the removal of the hemicellulose fraction of lignocellulosic material. Infrared there are changes in the absorption bands relating hemicellulose due to its removal, and modification of the lignin and cellulose bands due their increase. The thermogravimetric curve taken characteristic similar to the aftertreatment acid cellulose, as this is the component in larger amounts in the biomass. The micrographs showed the breakdown of fibrous regions of the cellulose fibrils and decrease in the interconnected, and these hemicellulose. In the XRD crystallinity index indicated extensive removal of the amorphous fraction of the lignocellulosic material. In the fermentation was carried out the study of the microorganism to be used, it is the best time to perform the inoculum, under the conditions that the medium contained 3 g/L or 107 cells and were observed three main stages of growth of the microorganism. Both the dry mass analysis as the cell count per chamber Neubauer the best time for completion of the fermentation was between 24 and 36 h. It was found that the best fermentation times for xylitol was 72 h and the ethanol was 36 h, yielding respectively 1.4 g/L and 2.4 g/L in Candida guilliermondii.